Early Stages of Morpho amathonte (Lepidoptera: Nymphalidae, Morphinae) and its Variation on the Pacific Coast of Costa Rica - Córdoba-Alfaro, Jim (2017)
The Southern Pacific Coast of Costa Rica shows some local variations in its four Morpho species. The goal of this article is to compare the life cycle of M. amathonte from different areas in Costa Rica and South America. The immature stages were found on Pterocarpus officinalis Jacq. and then photographed and described so as to illustrate its morphology and behavior. It is clear, that M. amathonte from the South Pacific side of Costa Rica comes from one isolated population and demonstrates a cryptic nature between the two forms present in Costa Rica.